The Influence of Philanthropy Disclosure and Systematic Risk on Company Value with Company Size as a Moderating Variable - Damayanthi, I Gst Ayu Eka; Andreana, Made Oka Candra; Amara, Anisa Virdawati; Purwanti, Ni Kadek Dian; Pratiwimba, Putu Dhira (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p08, 2025)
This study aims to obtain empirical evidence on the effect of philanthropy disclosure and systematic risk on firm value using firm size as a moderating variable. The population in this study were mining companies listed on the IDX for the 2019-2023 period. The results of sample selection using the purposive sampling method totaling 276 companies were analyzed using the moderation regression analysis technique. The results of the study indicate that philanthropy disclosure has a positive effect on firm value, systematic risk has a negative effect on firm value. Firm size weakens the positive effect of philanthropy disclosure on firm value, but strengthens the negative effect of systematic risk on firm value. The theoretical implications of this study are able to confirm the signal theory and stakeholder theory based on the results of the hypothesis tests conducted. The practical implications of this study provide information to investors and managers regarding factors that can be considered in assessing a company. Keywords :   Firm size;  Firm value;  Philanthropy disclosure;  Systematic risk